3D Neuronal Networks: Multiscale Modulation of Nanocrystalline Cellulose Hydrogel via Nanocarbon Hybridization for 3D Neuronal Bilayer Formation (Small 26/2017). Issue 26 (July 2017) - Kim, Dongyoon; Park, Subeom; Jo, Insu; Kim, Seong‐Min; Kang, Dong Hee; Cho, Sung‐Pyo; Park, Jong Bo; Hong, Byung Hee; Yoon, Myung‐Han
Abstract : Non‐genetic control over bacterial cellulose synthesis and the application for functional neuronal network formation is demonstrated in article number1700331, by Byung Hee Hong, Myung‐Han Yoon, and co‐workers. Hybridization of bacterial cellulose with graphene oxide by dispersion of nanocarbon flakes in bacterial culture medium delicately modulates the resultant cellulose network properties and 3D nanofiber orientations. The nanocarbon‐hybridized bacterial cellulose successfully supports the 3D culture of dissociated hippocampal neurons with well‐defined bilayer network formation.